Treatment of Acute Complications of Diabetes Mellitus - Vidyashree S. Hulkoti; Yash Gupte; Sourya Acharya (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Diabetes mellitus is associated with grave immediate complication. These complications if not managed effectively and vigorously can result in increased mortality. Diabetic Ketoacidosis, Hyperosmolar hyperglycemic state and hypoglycaemia are few such complication. Paramount attention is mandatory for life saving management of these complications.